Tuneable CO2 binding enthalpies by redox modulation of an electroactive MOF-74 framework. Issue 6 (1st March 2021) - Doheny, Patrick W.; Babarao, Ravichandar; Kepert, Cameron J.; D'Alessandro, Deanna M.
Abstract : Chemical reduction of an electroactive metal–organic framework based on napthalenediimide modulates carbon dioxide uptake and heat of adsorption. Abstract : The [M2 (dobdc)] series of frameworks (also known as MOF-74 and CPO-27, where M 2+ = Zn, Mg, for example, and dobdc 2− = 4, 6-dioxido-1, 3-benzenedicarboxylate) have been the subject of enormous interest in respect to their attractive gas adsorption properties that arise from the ultra-high concentration of open metal sites. An interesting prospect with respect to future applications of these materials is the possibility of generating a 'switchable' framework in which the guest adsorption can be modulated by virtue of the redox state of the framework. Herein, we report a closely related metal–organic framework (MOF), [Zn2 (DSNDI)], where the redox state of the electroactive ligand DSNDI 4− ( N, N ′-bis(4-carboxy-3-hydroxyphenyl)-1, 4, 5, 8-naphthalenetetracarboxydiimide) can be modulated using both in situ and ex situ methods. The material is stable to both chemical and electrochemical reduction of its organic DSNDI units without structural collapse or degradation, and remains porous to N2, H2 and CO2 . The chemically reduced frameworks demonstrate notable changes from the parent material, particularly with respect to CO2 binding. The CO2 isosteric heat of adsorption ( Q st ) increases from 27.9 kJ mol −1 in the neutral material to 43.9 kJ mol −1 after reduction due to enhanced host–guest interactions, the latter being comparable to the best performing member of the MOF-74 series, [Mg2 (dobdc)]. The origin of the enhanced interaction was probed using Density Functional Theory (DFT) calculations which corroborated the presence of enhanced framework-CO2 interactions for the chemically-reduced MOF. The tuneable CO2 binding character provides an attractive mechanism to tune gas separations and capture.